The Effect of Financial Inclusion on the Sustainability of the SME Sector - Zebua, Feberia; Bate’e, Maria Magdalena; Hulu, Perlindungan F. (Manunggal Halim Jaya, 2024)
This study aims to determine whether financial inclusion has a positive effect on the sustainability of the SME sector in Lotu District, North Nias Regency, and to determine how much influence financial inclusion has on the sustainability of the SME sector, and to find out whether financial inclusion can overcome the challenges experienced by SME actors. The research was conducted in Lotu District, North Nias Regency. The research method used is quantitative method with data collection through distributing questionnaires, documentation, and interviews, observation. Respondents in this study amounted to 63 respondents of SME actors. The results of this study indicate that the influence of financial inclusion has an influence on the sustainability of the SME sector by 20.4%. With the increasing financial inclusion, it will further encourage SME actors to develop their businesses in the future.